MODEL PENCEGAHAN FRAUD PADA ALOKASI DANA DESA DI DESA GABUS KABUPATEN PATI - Fuad, Khoirul; Mustaqin, Khoyrul (Universitas Sarjanawiyata Tamansiswa, 2024)
The amount of village fund allocation, considered quite large, is a big responsibility for village officials to manage the village funds. In a situation like this, it is possible to create the potential for the village government to make deviations. These deviations can occur individually, even the riskiest, namely in groups. This happens because of 3 conditions commonly referred to as the